Interactive Visualization of Multivariate Statistical Data - Chen, Jim X.; Carr, Daniel B.; Wechsler, Harry; Pan, Zhigeng (International Journal of Virtual Reality, 2006)
This paper introduces web-based interactive Linked Micromap (LM) plots, a set of dynamic visualization methods that allows readers to interactively select variables and modify the different views to help reveal relationships among the study units. This methodology provided the foundation for web-based micromaps used by the National Cancer Institute (NCI). This illustrates the power of visualization to make statistical summaries involving health and risk factors for millions of people accessible to health planners than may have never had a statistics class. LM plots methodology is in use by the Department of Agriculture and readily extend to other application in other agencies in the United States. The interactive methods can be as useful in such extensions as they were for the National Cancer Institute